Assessment strategies for knowledge organizations - Testa, Dean; Brown-Grant, Johel; Bedford, Denise (Emerald Publishing Limited, 2019)
As organizations transform from an industrial to knowledge-based economy, assessment strategies are rarely adapted to the new environment. Offering an enhanced understanding of how to engage organisations in assessments, this is an unmissable book for knowledge management professionals and researchers.
Includes index.
Keywords: Knowledge economy.; Knowledge management.; Business & Economics -- Economics -- General.; elektronické knihy; electronic books